2014
DOI: 10.1007/s11606-014-2795-z
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Associations Between Clinicians’ Ethnic or Racial Bias and Hypertension Treatment, Medication Adherence and Blood Pressure Control

Abstract: BACKGROUND: Few studies have directly investigated the association of clinicians' implicit (unconscious) bias with health care disparities in clinical settings. OBJECTIVE: To determine if clinicians' implicit ethnic or racial bias is associated with processes and outcomes of treatment for hypertension among black and Latino patients, relative to white patients. RESEARCH DESIGN AND PARTICIPANTS: Primary care clinicians completed Implicit Association Tests of ethnic and racial bias. Electronic medical records we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 43 publications
(63 reference statements)
2
70
1
1
Order By: Relevance
“…Thus, while implicit bias may not lead to overt discrimination, when the provider and the patient come from different cultural or racial groups, health providers may be less effective at establishing a good rapport with their clients (Blair et al, 2014). Dovidio, Kawakami and Gaertner (2002) have shown that implicit attitudes "leak" during interactions through the display of negative non-verbal behaviours, meaning that those with higher implicit biases may be perceived as less friendly by out-group minorities.…”
Section: Non-mäori Perspectives and The Role Of Implicit Biasmentioning
confidence: 99%
“…Thus, while implicit bias may not lead to overt discrimination, when the provider and the patient come from different cultural or racial groups, health providers may be less effective at establishing a good rapport with their clients (Blair et al, 2014). Dovidio, Kawakami and Gaertner (2002) have shown that implicit attitudes "leak" during interactions through the display of negative non-verbal behaviours, meaning that those with higher implicit biases may be perceived as less friendly by out-group minorities.…”
Section: Non-mäori Perspectives and The Role Of Implicit Biasmentioning
confidence: 99%
“…Annals of Internal Medicine published just 29 articles over this same time period). While as a society we have not come close to former Surgeon General Dr. David Satcher's call to eliminate health disparities by the year 2010, JGIM has continued to shine a light on this shameful national tragedy by featuring high-quality original research that not only underscores the impact of racial and ethnic disparities, but also has broadened the scope of research on health disparities to include discrimination against persons with certain diseases such as sickle cell anemia 1 , discrimination against sexual minorities 2 , and groundbreaking work on the insidious influence of unconscious bias on health care delivery 3 .…”
Section: O Ver the Past Ten Years The Journal Of General Internalmentioning
confidence: 99%
“…Many of these studies were conducted by measuring physicians' level of implicit bias against racial/ethnic minorities using the well-validated Implicit Associations Test (IAT), 2 and then linking the level of bias to provider behavior or decision making in clinical simulations, scenarios and vignettes. 3 However, when observing how a physician behaves or responds to a hypothetical vignette or scenario, it is not physician behavior that is being measured; rather, it is the physician's behavioral intention in the given scenario or vignette, which is not always predictive of actual behavior. Thus, more research that examines physicians' unconscious bias in the context of their actual behavior (with actual patients) is needed.…”
mentioning
confidence: 99%
“…3 In a well-designed study, the authors administered IATs to 138 primary care physicians across two health systems in Colorado. Next, via electronic medical record review, hypertension-related process and clinical outcomes of 4,794 Black, Latino and white patients cared for by the 138 participating physicians were examined and modeled for associations with physician biases.…”
mentioning
confidence: 99%
See 1 more Smart Citation